The impact of COVID-19 on earnings management: evidence from South Africa - Mpumpula, Asanda (College of Accounting, 2025)
This study aims to determine whether the COVID-19 pandemic impacted the earnings management practices of South African firms and various industries by assessing the quality of total accruals. The study used discretionary accruals as a proxy for the magnitude of earnings management activities, estimated using the Modified Jones Model adapted by Kothari et al. (2005). 2016 to 2019 was deemed the pre-crisis period, while 2020 to 2022 was deemed the crisis period. The discretionary accruals of a sample of 159 Johannesburg Stock Exchange-listed firms were observed to determine the impact of COVID-19 on earnings management. Further, due to how different the impact of COVID-19 and the lockdown protocols were on the various industries, earnings management practices across the industries were observed. The findings suggest that COVID-19 had a significant impact on earnings management. Firms were found to engage in income- decreasing discretionary accruals during the crises. Further, the industry analysis suggests that the impact of COVID-19 on the industries observed was not symmetrical. A statistically significant increase in income-decreasing discretionary accruals was observed in basic metals, consumer discretionary and the technology industry. Consumer staples, health care and the telecommunications industry that were deemed to provide essential services during the pandemic were found to have increased their discretionary accruals and utilised income-decreasing accruals; however, the difference between pre- crisis and crisis-period discretionary accruals is not statistically significant. The study results also found that the energy and industrials industry decreased their discretionary accruals and improved the quality of accruals reported during the pandemic. This study adds to the limited research on earnings management in South Africa, an emerging market with characteristics of a developed country. This study may be useful for standard setters in their mandate to improve reporting standards and thus the quality of financial reports, investors seeking to value companies accurately, and regulators of financial statements concerned with the quality of financial reports in South Africa, such as the JSE and the South African Institute of Chartered Accountants.